2005
DOI: 10.1136/gut.2003.031435
|View full text |Cite
|
Sign up to set email alerts
|

Dietary carbohydrates and glycaemic load and the incidence of symptomatic gall stone disease in men

Abstract: Background: Diets with a high glycaemic response exacerbate the metabolic consequences of the insulin resistance syndrome. Their effects on the incidence of gall stone disease are not clear, particularly in men. Methods: Dietary information was collected as part of the Health Professionals Follow up Study starting in 1986 using a semiquantitative food frequency questionnaire with follow up until 1998. On biennial questionnaires participants reported new symptomatic gall stone disease, diagnosed by radiology, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Indeed, all the above have been associated as risk factors for cholesterol gallstones in large epidemiological data sets from the USA, Europe, Japan, and China [11,12,13,14,15,16]. In a Japanese cohort of 1,264 patients, Tsunoda et al [16] reported a strong positive correlation between calories consumed and gallstone formation.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, all the above have been associated as risk factors for cholesterol gallstones in large epidemiological data sets from the USA, Europe, Japan, and China [11,12,13,14,15,16]. In a Japanese cohort of 1,264 patients, Tsunoda et al [16] reported a strong positive correlation between calories consumed and gallstone formation.…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Data from two large US prospective epidemiological association studies using cohorts from the Health Professionals Follow-Up Study (men) and the Nurses’ Health Study (women) found a high intake of carbohydrate, coupled with an increased dietary glycaemic load, to enhance the risk of symptomatic gallstone disease and cholecystectomy in men and women, respectively [13,14]. In particular, refined sugar is often positively correlated with gallstone risk, as evidenced in these two cohorts in addition to several other studies [17,18,19,20].…”
Section: Lifestyle Factorsmentioning
confidence: 99%
“…Low fat high carbohydrate diets of a high glycemic index have been associated with symptomatic gall bladder disease (Tsai et al 2005) likely due to reduced cycling of cholesterol through bile salt release. Although fat or oil are often stated as affecting gastrooesophagial reflux disease, a systematic review of the literature failed to find an effect of fat consumption (Dent et al 2005).…”
Section: Health Effects Of Fat As a Macronutrient And Energy Sourcementioning
confidence: 99%
“…Over a third (36%) of these trials were studies with a duration of <1 day. All 11 cohort studies [16][17][18][19][20][21][22][23][24][25][26] were conducted in adults, of which eight were in healthy populations, one in pregnant women, one in diabetics, and one in a study population with mixed health status. The sample sizes of these cohorts were large (mean sample size = 35,738) with a wide range of follow-up time (4 to 48 years).…”
Section: Resultsmentioning
confidence: 99%
“…None lasted for more than one year. Of the 11 cohort studies [16][17][18][19][20][21][22][23][24][25][26], one study in adults investigated the relationship between simple or added sugars and change in waist circumference after five years [20].…”
Section: High Priority Research Questionmentioning
confidence: 99%